Performance Analysis Of Phase Encoded OCDMA System In Dispersive Fiber Medium - Chua, Choon Hoe (2004)
Performance analysis of an asynchronous phase-encoded optical code-division multiple-access system is evaluated in a dispersive fibre medium. An analytical expresssion for the root mean square(rms) width of the phase encoded signal (pseudorandom optical signal with low intensity) propagating in linear dispersive fibre is derived.